SUMBER STRES, STRATEGI KOPING, DAN TINGKAT STRES PADA BURUH PEREMPUAN BERSTATUS MENIKAH DAN LAJANG - Oktaria, Ria; Krisnatuti, Diah; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
This study aimed to analyze the differences between characteristics, sources of stress, coping strategies, and stress level based on marital status (married and single) and also to analyze the influence of characteristics, sources of stress, and coping strategies on stress levels of women workers. The study was conducted in the TBG garment factory, Bogor City, West Java. The study involved 120 women workers (60 married women workers and 60 single women workers) that was selected by stratified random sampling. Data was collected by interview and was analyzed by descriptive analysis, independent samples t-test, and multiple linear regression. The results showed that age, income, sources of stress, and coping strategies of married woman worker was higher than single women worker, whereas stress level of married women worker is lower than single women worker. The increasing of income per capita and emotional focus coping can decrease stress level of women worker.